Promoting inclusive engineering identities in first-year engineering courses: poster - Atadero, Rebecca A., author; Paguyo, Christina H., author; Rambo-Hernandez, Karen E., author; Henderson, Heather Lysbeth, author (Colorado State University. Libraries, 2016)
Project goal: Change engineering culture to support robust learning in degree programs, more effective professional practice, and efforts to retain diverse students and professionals.
Presented at the ASEE's 123rd Annual Conference & Exposition in New Orleans, Louisiana, USA, June 26-28, 2016.
Keywords: engineering education; diversity in engineering; first-year engineering students; engineering identity; women; underrepresented minorities; inclusive engineering; engineering curriculum